Back extensor and psoas muscle cross-sectional area, prior physical training, and trunk muscle strength - a longitudinal study in adolescent girls - Peltonen, J. E.; Taimela, S.; Erkintalo, M.; Salminen, J. J.; Oksanen, A.; Kujala, U. M. (European Journal of Applied Physiology, 1997)
The association between physical training, low back extensor (erector spinae plus multifidus muscles) and psoas muscle cross-sectional areas (CSA) and strength characteristics of trunk extension and flexion were studied in adolescent girls. A group of athletes ( n=49) (age range 13.7-16.3 years) consisting of gymnasts, figure skaters and ballet dancers was age-matched with non-athletes ( n=17) who acted as a sedentary control group. The CSA of psoas muscles and multifidus plus erector spinae muscles were measured from lumbar axial images by magnetic resonance imaging. Maximal trunk extension and flexion forces were measured in a standing position using a dynamometer and trunk musculature endurance was evaluated using static holding tests. When CSA were adjusted with body mass, the athletes showed significantly greater CSA in both muscles studied.